Analisis Pembelajaran Berdiferensiasi sebagai Strategi Meningkatkan Keaktifan Peserta Didik Kelas IV SDN Plamongansari 02 - Putri Sukrotin Ni’mah; Muhammad Prayito; Joko Sulianto; Darsino Darsino (Departement of Mathematics Education, 2023)
Active student learning in the learning process can stimulate and develop their talents, think critically and be able to solve problems in everyday life. The activeness of students affects their success in learning and their learning outcomes. This study aims to analyze student learning activeness with differentiated learning strategies in fourth grade students at SDN Plamongansari 02. The research method used is descriptive qualitative. The subjects of this study were class teachers and fourth grade students at SDN Plamongansari 02. The research data collection techniques used were interviews and observation. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. Based on the research conducted, it was found that differentiated learning in the content of science lessons in class IV SDN Plamongansari 02 which was carried out could foster students' active learning towards science subject matter. The application of learning with a differentiated learning approach to the content of science lessons obtained good learning outcomes and positive responses from fourth grade students at SDN Plamongansari 02 even though there were obstacles that occurred in the learning faced by the teacher.